Chicken in the kitchen - Johnston, Tony, 1942- (Simon & Schuster Books for Young Readers, 2005)
When a crazy chicken wreaks havoc in the kitchen there is just one thing to do--prepare a nest so that she will settle down. A restless little chicken is flap, flap, flapping her way through a kitchen. But why is she there? What could she be looking for? Follow the excitement and find out all the little reasons that have driven this chicken to peck and pick and poke!